A comparison of field methods to estimate Canada goose abundance. (8th November 2017) - McAlister, Mark A.; DePerno, Christopher S.; Fuller, Joseph C.; Howell, Douglas L.; Moorman, Christopher E.
ABSTRACT: We conducted a 2‐year study (2014–2015) in North Carolina, USA, to compare precision and efficiency between 2 methods used to estimate Canada goose ( Branta canadensis ) abundance. The first method (i.e., band‐return estimation) used hunter band‐returns and harvest estimates. The second (i.e., plot survey) used surveys of 1‐km 2 plots randomly located across potential goose habitat in the state. To quantify efficiency, we recorded all expenses and time dedicated to goose banding and plot surveys. In June 2014, we banded 2, 102 adult geese at 44 sites. During the 2014–2015 hunting season, we received 173 direct band recoveries from birds banded as adults. We used the Lincoln–Peterson formula to calculate an abundance estimate of 148, 839 (coeff. of variation = 7.9) and determined the band‐return method required US 72, 858 and 2, 317 person‐hours to complete. We surveyed 300 1‐km 2 plots across North Carolina in April 2015, and calculated an abundance estimate of 155, 655 Canada geese (coeff. of variation = 308.9). We determined the plot‐survey method required US 80, 767 and 2, 857 person‐hours to complete. Although population estimates were similar, we recommend the band‐return technique to estimate Canada goose abundance because it provided a more precise estimate with similar overall costs and, if continued for multiple years, will allow calculation of additional population metrics including survival, recovery rates, and harvest distributions. © 2017 The Wildlife Society. Abstract : We compared precision and efficiency between the band‐return and plot‐survey methods to estimate temperate‐breeding Canada goose ( Branta canadensis ) abundance. Population estimates were similar, but we recommend the band‐return method to estimate Canada goose abundance because it provided a more precise estimate with similar overall costs and, if continued for multiple years, will allow calculation of additional population metrics.